1980
DOI: 10.1037/0022-3514.39.4.590
|View full text |Cite
|
Sign up to set email alerts
|

Racial and behavioral cues in Black and White children's perceptions of ambiguously aggressive acts.

Abstract: To explore the way in which the interpretation of ambiguous social behavior can be influenced by racial stereotypes and cultural differences, 40 black and 40 white 6th-grade males were shown a variety of ambiguously aggressive behaviors performed by black and white stimulus figures. As predicted, both black and white preadolescents rated these behaviors as more mean and threatening when the perpetrator was black than when he was white. In contrast, ratings of personal characteristics were in general determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
302
4
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(322 citation statements)
references
References 11 publications
14
302
4
2
Order By: Relevance
“…and inconsistent behaviors (Bodenhausen & Wyer, 1985;Darley & Gross, 1983;Duncan, 1976;Krueger & Rothbart, 1988;Kunda & Sherman-Williams, 1992;Sagar & Schofield, 1980). Prior research has also shown that traits are more likely to be inferred spontaneously from stereotype-consistent than stereotype-inconsistent behaviors (e.g., Wigboldus et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and inconsistent behaviors (Bodenhausen & Wyer, 1985;Darley & Gross, 1983;Duncan, 1976;Krueger & Rothbart, 1988;Kunda & Sherman-Williams, 1992;Sagar & Schofield, 1980). Prior research has also shown that traits are more likely to be inferred spontaneously from stereotype-consistent than stereotype-inconsistent behaviors (e.g., Wigboldus et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the same ambiguous behavior is perceived as more aggressive when performed by a Black than a White target (Duncan, 1976;Sagar & Schofield, 1980; see also Bodenhausen & Wyer, 1985;Darley & Gross, 1983;Krueger & Rothbart, 1988;Kunda & Sherman-Williams, 1992). As such, it might be expected that stereotypes would influence the likelihood that trait inferences would be drawn spontaneously from observed behaviors.…”
mentioning
confidence: 99%
“…In the real world, subjects are free to use alternative and possibly more immediate strategies of language use to distinguish ingroup and out-group behaviors. For example, they may simply use different terms within the same linguistic category (e.g., a behavior that is described as "playful" when displayed by an ingroup member may be interpreted as "aggressive" when ascribed to an out-group member;, see Duncan, 1976;Sagar & Schofield, 1980). It is possible that the linguistic intergroup bias is displayed only in situations in which people are prevented from using other strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In other research, participants who watched a video of a heated argument and pushing behaviors were significantly more likely to rate the actor as engaging in violent behavior if he was Black instead of White (Duncan, 1976). Similarly, Sagar and Schofield (1980) found that sixth grade boys interpreted vaguely aggressive but innocuous behaviors (e.g., bumping in the hallway, requesting food from others, poking a student, and using another's pencil without permission) to be more threatening when displayed by Black versus White targets.…”
Section: Priming and Stereotype Researchmentioning
confidence: 99%